2012
DOI: 10.3846/13923730.2012.731252
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Deformation State of the Double-Wave Guardrail Mounted on Bridges and Viaducts of the Motor Roads in Lithuania and Ukraine

Abstract: Traffic safety mainly depends on vehicles, pedestrians and road infrastructure. On highways, the heaviest traffic accidents are associated with crossing of the dividing strips by a vehicle and its collision with side obstacles on the junction or road bridge exit. These accidents often occur, when vehicles, running at a high speed, collide with obstacles, which may cause human injuries. In such cases, the probability of fatalities or heavy injuries to people in a traffic accident is very high. Road traffic infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…While the use of FE modelling systems has been established for the application in structural engineering not only for static but also dynamic analysis (with both elastic and large plastic deformations), it can be observed that in par-ticular on the US American market there is a strong party to favour the FE code LS-DYNA to simulate vehicle impacts to VRSs (Neuenhaus et al 2013). This trend is followed also on the European market (e.g., Ren and Vesenjak 2005;Borovinšek et al 2007;Reid et al 2009;Prentkovskis et al 2010Prentkovskis et al , 2012.…”
Section: Safety Barriers and Elements Of Vehicle Restraint Sytemsmentioning
confidence: 81%
“…While the use of FE modelling systems has been established for the application in structural engineering not only for static but also dynamic analysis (with both elastic and large plastic deformations), it can be observed that in par-ticular on the US American market there is a strong party to favour the FE code LS-DYNA to simulate vehicle impacts to VRSs (Neuenhaus et al 2013). This trend is followed also on the European market (e.g., Ren and Vesenjak 2005;Borovinšek et al 2007;Reid et al 2009;Prentkovskis et al 2010Prentkovskis et al , 2012.…”
Section: Safety Barriers and Elements Of Vehicle Restraint Sytemsmentioning
confidence: 81%
“…They may negatively affect serviceability of a road in relation to position and size on deformed pavement surface and work zone (Aydın 2012;Ghasemlou et al 2016). They also have a significant impact on vehicle speed, traffic flow conditions and traffic accidents (Akgüngör, Doğan 2009;Prentkovskis et al 2010Prentkovskis et al , 2012Dell' Acqua, Russo 2011;Aydın, Topal 2016;Dell' Acqua et al 2016). Deformations limit driving properties such as vehicle control, driving comfort and also cause an increasing on traffic accidents, vehicle operating and maintenance costs.…”
Section: Introductionmentioning
confidence: 99%
“…On highways, the heaviest traffic accidents are associated with crossing the dividing strips by a vehicle and its collision with side obstacles on the junction or road bridge exit (Prentkovskis et al 2012). The authors of the paper present the analysis of the deformation state of a double-wave guardrail (describing strains and stresses of its elements).…”
mentioning
confidence: 99%